Convergence and hybrid information technology 6th International Conference, ICHIT 2012, Daejeon, Korea, August 23-25, 2012. proceedings - Lee, Geuk (Lecture notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 6th International Conference on Convergence and Hybrid Information Technology, ICHIT 2012, held in Daejeon, Korea, in August 2012. The 94 revised full papers presented were carefully reviewed and selected from 196 submissions. The papers are organized in topical sections on communications and networking; HCI and virtual reality; image processing and pattern recognition; hardware design and applications; computational biology and medical information; data mining and information retrieval; security and safety system; software engineering; workshop on advanced smart convergence (IWASC)